A Low-Stress, Elastic, and Improved Hardness Hydrogenated Amorphous Carbon Film. (4th August 2015) - Wang, Qi; He, Deyan; Zhang, Junyan
Abstract : The evolution of hydrogenated amorphous carbon films with fullerene-like microstructure was investigated with a different proportion of hydrogen supply in deposition. The results showed at hydrogen flow rate of 50 sccm, the deposited films showed a lower compressive stress (lower 48.6%), higher elastic recovery (higher 19.6%, near elastic recovery rate 90%), and higher hardness (higher 7.4%) compared with the films deposited without hydrogen introduction. Structural analysis showed that the films with relatively high sp 2 content and low bonded hydrogen content possessed high hardness, elastic recovery rate, and low compressive stress. It was attributed to the curved graphite microstructure, which can form three-dimensional covalently bonded network.